A new species of Polyonyx Stimpson, 1858 (Crustacea: Decapoda: Anomura: Porcellanidae) from the Philippines and Loyalty Islands - Osawa, Masayuki (Zootaxa, 2007)
A new porcellanid crab, Polyonyx spina, is described from the Philippines and Loyalty Islands. Among the Indo-West Pacific species of the genus, the spines on the flexor margins of the meri of the ambulatory legs are found only in the new species and P. pedalis Nobili, 1905. Polyonyx spina is distinguished from P. pedalis by the shape of the carapace and third thoracic sternite, and the strength of spines on the meri of the ambulatory legs.